2014
DOI: 10.4209/aaqr.2013.06.0221
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Mixing of Size Resolved Traffic Induced and Background Ultrafine Particles from an Urban Street Canyon to Adjacent Backyards

Abstract: By means of numerical simulations the aims of this study are as follows: (1) to investigate the dispersion and mixing of ultrafine particles (UFP) with pre-existing size resolved UFP in a street canyon and its vicinity with the ENVI-met 3D microscale model; (2) to show the effects of boundary conditions, like wind direction and traffic emissions, on the UFP concentration in the near vicinity; and (3) to evaluate the importance of deposition and coagulation at the street scale. The decrease in UFP concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 45 publications
(53 reference statements)
2
19
0
Order By: Relevance
“…Most of the researches have shown that both local rush hour traffic emission and new particle formation (NPF) play key roles in the diurnal variation of UFPs concentrations, in which two concentration peaks in the morning and evening could be attributed to traffic emission, while one peak in the afternoon is due to NPF (Young et al, 2012;Cheung et al, 2013;Young et al, 2013;Betha et al, 2014;Nikolova et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the researches have shown that both local rush hour traffic emission and new particle formation (NPF) play key roles in the diurnal variation of UFPs concentrations, in which two concentration peaks in the morning and evening could be attributed to traffic emission, while one peak in the afternoon is due to NPF (Young et al, 2012;Cheung et al, 2013;Young et al, 2013;Betha et al, 2014;Nikolova et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…One explanation for this deficiency is that the methods developed for monitoring and modelling at larger scales are inappropriate for microscale phenomena (Woo et al 2011). However, increasing numbers of MSAQ models (Bruse and Fleer 1998, Chang and Meroney 2003, Chu et al 2005 and other studies (Vos et al 2013, Nikolova et al 2014) are trying to overcome these limitations. Therefore, the present study focused on the development and validation of GS to enable comparisons in the context of MSAQ.…”
Section: Methodsmentioning
confidence: 97%
“…Dry deposition and coagulation of particles were identified to be the most important aerosol dynamic processes that control the evolution and removal of particles. However, CFD calculations on a street canyon for different wind directions by Nikolova et al [158] revealed that the overall effect of deposition and coagulation on the UFP is negligible for the cases considered. They conclude that overall, deposition is more efficient and faster than coagulation in removing particles, and especially those in the nucleation mode.…”
Section: Near-source Processes: Coagulation Versus Dry Depositionmentioning
confidence: 97%